Optimal Power Flow using the Moth Flam Optimizer: A Case Study of the Algerian Power System - Bachir Bentouati; Lakhdar Chaib; Saliha Chettih (Institute of Advanced Engineering and Science, 2016)
In this paper, a new technique of optimization known as Moth-Flam Optimizer (MFO) has been proposed to solve the problem of the Optimal Power Flow (OPF) in the interconnected power system, taking into account the set of equality and inequality constraints. The proposed algorithm has been presented to the Algerian power system network for a variety of objectives. The obtained results are compared with recently published algorithms such as; as the Artificial Bee Colony (ABC), and other meta-heuristics. Simulation results clearly reveal the effectiveness and the robustness of the proposed algorithm for solving the OPF problem.